STUDI KOMPARASI MOTIF BATIK PARANG RUSAK BARONG GAYA YOGYAKARTA DAN GAYA SURAKARTA - Renta Vulcanita Hasan (LITERASI: Indonesian Journal of Humanities, 2012)
This article discusses the batik design of Parang Rusak Barong found in Yogyakarta and Surakarta palaces, as the centres of cultural development. The factors explaining the the commonalities and differences are examined both internally and externally. The research is qualitative in nature and employes multidisiplinary approach focusing on fine arts. The fine arts approach adopted here is the aesthetic one. This approach is complentarily supported by theories originating from history, communication, anthropology, archeology, and sosiology. The major commonalities and differences between Parang Rusak Barong batik design of Yogyakarta and that of Yogyakarta is found in the form and colour structures. The form meant here is the line composition forming isenisen design, while colour meant here is the intensity found in the design. Thera are no commonalities and differences in terms of function and meaning. The factors responsible for the fissures and commonalities are: internally regulations and policies issued by each palace, and externally, the developing socioeconomic conditions and the policies of the Indonesian government in tourism sector and batik standardization in Indonesia.Keywords: batik design, comparation, Parang Rusak Barong, Surakarta, Yogyakarta